Membangun Transparansi Pengelolaan Keuangan Desa: Peran Kompetensi, Komitmen, dan Pengawasan - Syamsul, Syamsul; Nurlailah, Nurlailah; Nurhadi, Nurhadi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2026)
This study aims to analyze the effects of village facilitator competence, village government commitment, and oversight by the Village Consultative Body (BPD) on the transparency of village financial management. Employing an explanatory quantitative design, the research was conducted in villages in Donggala Regency. Data were collected through a survey of village government officials, BPD members, and community leaders, and subsequently analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that village facilitator competence, village government commitment, and BPD oversight each have a positive and significant effect on the transparency of village financial management. These findings underscore the importance of strengthening the capacity of village facilitators, ensuring the consistency of village government commitment, and enhancing the effectiveness of the BPD's oversight function in promoting information transparency and reducing information asymmetry in village financial management.